PENYULUHAN PENTINGNYA PERILAKU HIDUP BERSIH DAN SEHAT DENGAN MENINGKATKAN ASUPAN GIZI SEIMBANG PADA MASA PANDEMI - Rika Indriani Rukmana Putri; Kholifatus Sa’diyah; Aniswatul Mukmila; Diyah Ayu Widyaningrum (JPM PAMBUDI, 2022)
The community in the village of Ringinasri Sumbermanjing wetan has not fully implemented the Clean and Healthy Lifestyle (PHBS) during the COVID-19 pandemic. This can be seen in students at MA-Al Hisi who have not implemented health protocols and have not paid attention to balanced nutrition as a daily nutritional intake. The solution to overcome this problem is through counseling with the theme of the importance of clean and healthy living behavior during the pandemic. The research procedure includes preliminary, core and final activities. The research instrument used a questionnaire. The results of the questionnaire show that most of the students have understood about clean and healthy living behavior after being given counseling.